2007
DOI: 10.1523/jneurosci.2992-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Substance P and Neurokinin A to the Differential Injury-Induced Thermal and Mechanical Responsiveness of Lamina I and V Neurons

Abstract: In a previous report, we compared the properties of lamina V neurons of the spinal cord dorsal horn in wild-type mice and in mice with a deletion of the preprotachykinin-A (PPT-A) gene, which encodes substance P (SP) and neurokinin A (NKA). The mutant mice had pronounced deficits in the response to thermal stimulation, both before and after mustard oil induced sensitization. Here, we extended our analysis to the properties of lamina I neurons and also examined responsiveness to mechanical stimulation. Consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
3
12
1
Order By: Relevance
“…This is partially consistent with recent studies showing that AITC significantly enhanced murine deep dorsal horn WDR neuronal responses to only the weakest mechanical stimulus (130 mN) while having no significant effect on responses to stronger stimuli (Mazario and Basbaum 2007). However, other studies have shown significant enhancement of neuronal responses to innocuous mechanical stimuli, and expansion of receptive fields, in rats and mice after application of AITC adjacent to the mechanosensitive receptive field of spinal WDR or NS neurons (Pertovaara 1998;Weng et al 2001;Woolf and King 1990;Woolf et al 1994).…”
Section: Mechanically and Electrically Evoked Responsessupporting
confidence: 90%
See 1 more Smart Citation
“…This is partially consistent with recent studies showing that AITC significantly enhanced murine deep dorsal horn WDR neuronal responses to only the weakest mechanical stimulus (130 mN) while having no significant effect on responses to stronger stimuli (Mazario and Basbaum 2007). However, other studies have shown significant enhancement of neuronal responses to innocuous mechanical stimuli, and expansion of receptive fields, in rats and mice after application of AITC adjacent to the mechanosensitive receptive field of spinal WDR or NS neurons (Pertovaara 1998;Weng et al 2001;Woolf and King 1990;Woolf et al 1994).…”
Section: Mechanically and Electrically Evoked Responsessupporting
confidence: 90%
“…Previous studies of WDR neurons in lamina V of mice reported significant enhancement of neuronal responses to 40°C (but not 45 or 49°C) (Eckert 3rd et al 2006;Mazario and Basbaum 2007), and a significant enhancement of afterdischarge responses to 41 and 45°C (Martin et al 2004) after application of AITC (10%, ϳ60 l) to the hindpaw. Lamina I NS neuronal responses to heat were also enhanced post-AITC (Eckert 3rd et al 2006;Mazario and Basbaum 2007). Our results are generally consistent, in that AITC more strongly enhanced rat WDR neuronal responses to the lower stimulus temperatures (42 and 46°C) compared with the highest (50°C).…”
Section: Aitc and Ca Sensitization Of Heat-evoked Responsesmentioning
confidence: 91%
“…Apparently, heat and mechanical sensitization are dissociable and likely controlled by different mechanisms, as suggested by several other studies (Tal and Bennett, 1994;Ali et al, 1996;Mazarío and Basbaum, 2007). However, our behavioral results contradict the findings of Nassar et al (2004), who reported that sensitization to mechanical stimuli was absent after CFA in the same line of Na v 1.7 cKO mice that was used here.…”
Section: Discussioncontrasting
confidence: 54%
“…Lamina I and V neurons in mice that lack Sub P exhibit deficits in their response to noxious heat, but not to noxious mechanical stimulation. In addition, in mice lacking Sub P, MO-induced sensitization to heat stimuli was greatly reduced in these neurons, whereas sensitization to mechanical stimuli was retained (Mazario and Basbaum, 2007). Interestingly, Simone and colleagues recently reported that ablation of NK1 expressing RVM neurons by microinjection of saporin-Sub P more effectively reduced capsaicin- and CFA-induced thermal hyperalgesia than mechanical hypersensitivity (Brink et al, 2009).…”
Section: Discussionmentioning
confidence: 99%